Application of the power snatch for athletic conditioning - Waller, M.; Townsend, R. (Strength and Conditioning Journal, 2007)
The purpose of this article is to provide the strength and conditioning professional with the information to effectively implement the use of the power snatch for athletic development. Rationale for the use of the power snatch, along with a description of the technical aspects will be discussed.